Nahualismo, testimonio y medio ambiente. Una versión mesoamericana sobre la revolución - Lara Martínez, Rafael (2013)
This article analyzes the work of Alfredo Lopez Austin, Mexican historian specializing in Mesoamerican religion (Lopez Austin 1973, 1984, 1993, 1994, 1997a, 1997b / c). Specifically, we focus on the indigenous concept of "person" with multiple representations of the human soul (tonalli, yóllotl and ihíyotl), and in his tragic creation process. We try to explain the idea of a split I, who can project both souls and intimate experiences for the environment. This projection of souls to the outside world, deconstructs the Western dichotomy between nature and culture, between the environment and human inhabitant. The natural features such as trees, animals, rivers and stones contain their own spiritual strength, just like a human or divine soul, which is foreign to them. We also examined the dramatic process of creating natural-beings Mesoamerican version of Big Bang, through the removal and degradation of the divinities to historical world of human beings.